Influence of Light Spectrum on Bread Wheat Head Colonization by Fusarium graminearum and on the Accumulation of Its Secondary Metabolites - Minely Cerón-Bustamante; Francesco Tini; Giovanni Beccari; Andrea Onofri; Emilio Balducci; Michael Sulyok; Lorenzo Covarelli; Paolo Benincasa (Plants, 2025)
Previous studies indicated that light influences mycotoxin production and wheat’s defense responses to the cereal fungal pathogen Fusarium graminearum. Herein, the effect of different light wavelengths on F. graminearum colonization and secondary metabolite biosynthesis in bread wheat was assessed. Heads of a susceptible bread wheat cultivar were point-inoculated and exposed to red (627 nm), blue (470 nm), blue/red, and white light. Symptom severity, fungal DNA, and secondary metabolite accumulation were evaluated. Blue and red wavelengths reduced F. graminearum infection but had an opposite effect on the production of its fungal secondary metabolites. While blue light enhanced the accumulation of sesquiterpene mycotoxins, red light promoted the production of polyketide compounds. In addition, blue light stimulated deoxynivalenol glycosylation. These findings suggest that the light spectrum could affect mycotoxin contamination of wheat grains, highlighting the importance of light quality studies in field crops.